Does shared leadership fosters taking charge behaviors? A post-heroic leadership perspective in the public sector higher educational institutes. Issue 3 (12th August 2019) - Bilal, Ahmad Raza; Fatima, Tehreem; Imran, Muhammad Kashif
Abstract : Purpose: The purpose of this paper is to advance the theoretical perspective of complexity leadership paradigm to introduce shared leadership style as a precursor of taking charge behavior in public sector higher educational institutions (HEIs) of Pakistan. Moreover, this study unveils the underlying mechanisms of the climate of initiative and psychological safety for clarifying the link of shared leadership and taking charge. Design/methodology/approach: The multi-source and multi-wave data were analyzed by employing double mediation analysis (PROCESS Model 4); using 282 valid responses obtained from a proportionate stratified sample of faculty members working in public sector HEIs of Pakistan. Findings: The result indicates that shared leadership is a suitable style for governing the public sector HEIs and it fosters taking charge behavior in teaching faculty. Additionally, shared leadership creates climates that support initiatives and are psychologically safe that set stage for taking charge behaviors in teaching faculty of public sector HEIs of Pakistan. Originality/value: This research has filled the gap of focusing on more collaborative leadership styles instead of traditional vertical leadership practices in public sector HEIs of Pakistan. Theoretically, this study suggests new insights into the contextual antecedents and mediating mechanisms of taking charge behaviors.